2019
DOI: 10.1177/1753425919856078
|View full text |Cite
|
Sign up to set email alerts
|

Baicalin modulates apoptosis via RAGE, MAPK, and AP-1 in vascular endothelial cells during Haemophilus parasuis invasion

Abstract: Glässer’s disease, caused by Haemophilus parasuis, is a chronic disease related to an inflammatory immune response. Baicalin exerts important biological functions. In this study, we explored the protective efficacy of treatment with baicalin and the potential mechanism of activation of the MAPK signaling pathway in porcine aortic vascular endothelial cells (PAVECs) induced by H. parasuis. H. parasuis stimulated expression of receptor for advanced glycation end products, induced a significant increase in the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 42 publications
2
11
0
Order By: Relevance
“…Moreover, TIMP1 also plays an important role of anti-in ammatory and antinociceptive 18 , indicating that TIMP1 may be a critical component of a signalling cascade involved in reducing in ammatory hypersensitivity. H.parasuis infection activated the in ammatory signaling molecules and produced several pro-in ammatory cytokines in porcine cells 19,20 . Additionally, highly virulent H. parasuis infection increased a proportion of CD163 + monocytes in pigs, which are able to produce high amounts of proin ammatory cytokines, such as TNF-α, IL-1 and IL-6 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, TIMP1 also plays an important role of anti-in ammatory and antinociceptive 18 , indicating that TIMP1 may be a critical component of a signalling cascade involved in reducing in ammatory hypersensitivity. H.parasuis infection activated the in ammatory signaling molecules and produced several pro-in ammatory cytokines in porcine cells 19,20 . Additionally, highly virulent H. parasuis infection increased a proportion of CD163 + monocytes in pigs, which are able to produce high amounts of proin ammatory cytokines, such as TNF-α, IL-1 and IL-6 21 .…”
Section: Discussionmentioning
confidence: 99%
“…HMGB1 also participates in systemic fibrotic diseases through the RAGE/MAPK and NF-κB signalling pathways [ 42 ]. In a previous study, we showed that G. parasuis stimulated the release of HMGB1 in piglet PBMNs [ 22 ] and induced the activation of the RAGE and MAPK signalling pathways in porcine aortic vascular endothelial cells [ 20 ]. Therefore, we investigated whether HMGB1 is released and the MAPK signalling pathway is activated in piglets after challenge with G. parasuis .…”
Section: Discussionmentioning
confidence: 99%
“…Cell apoptosis is a type of programmed cell death that may contribute to the orderly and efficient removal of damaged cells [ 44 ]. In a previous study, we also showed that baicalin inhibits the apoptosis induced by G. parasuis via the RAGE and MAPK signalling pathways in vascular endothelial cells [ 20 ]. However, whether baicalin attenuates apoptosis in piglets challenged with G. parasuis has not been investigated until now.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Baicalin could inhibit the production of IL-6, IL-8, IL-10 and TNF-α and the phosphorylation of ERK, JNK and p38. Thereby activating the immune response induced by Th-1 to promoting the elimination of bacteria [ 105 ]. To sum up, SB play roles of anti-inflammatory, antibacterial and anti-viral via immune response.…”
Section: Pharmacological Effects (Shown In Table 2 mentioning
confidence: 99%